"Our One Great Hope": The Interdependence of the Woman's Relief Corps and the Grand Army of the Republic. Issue 3 (July 2022) - Chamberlain, Adam; Yanus, Alixandra B.
The Grand Army of the Republic (GAR) played a critical role in the lives of many Union veterans after the Civil War. Its efforts were supported by its women's auxiliary, the Woman's Relief Corps (WRC). Yet scholars do not know much about the evolution of the relationship between the rising WRC and the slowly declining GAR, whose members were dying away in the early 20th century. Here, we evaluate state-level membership and local group data for both associations to determine the nature of their connection from 1884 to 1924. The evidence reveals that the WRC's auxiliary role helped sustain the GAR while providing an organizational structure that allowed women to chart an independent course.